Penerapan Restorative Justice Dalam Perkara Korupsi Sebagai Wujud Peradilan Sederhana, Cepat, dan Biaya Ringan - Aksan Akbar; La Ode Awal Sakti; Faisal Herisetiawan Jafar (Universitas Semarang, 2023)
This study aims to determine the implementation of criminal law enforcement against perpetrators of corruption in Indonesia today and the application of the concept of restorative justice in the settlement of corruption cases in the future. This research is important to do as input to the legislature in the formation of laws in the future. The type of research used is normative legal research. This research has a novelty value, namely examining the application of the concept of restorative justice in the settlement of cases of corruption to make the principle of justice fast, simple and low cost effective. This research has a focus on the study of the application of the concept of restorative justice in the settlement of corruption cases in realizing a simple, fast and low-cost trial. The results of this study are as follows: First, the enforcement of criminal law for perpetrators of corruption in Indonesia is currently absolutely carried out through the judicial process, meaning that every criminal act of corruption, whether the amount of state financial losses is large or small, must go through a judicial process that ends with a criminal decision. Second, the application of the concept of restorative justice in solving corruption cases in this study only focuses on corruption cases where the loss is relatively small, which is carried out by returning state financial losses, giving fines and carrying out social work for perpetrators which involve perpetrators in their implementation. government and law enforcement officials. The application of the concept of restorative justice in the settlement of cases of corruption in addition to maximizing returns on state financial losses resulting from corruption, is also to reduce the use of state finances which are far greater than the state financial losses resulting from criminal acts of corruption. Penelitian ini bertujuan untuk mengetahui implementasi penegakan hukum pidana terhadap pelaku tindak pidana korupsi di Indonesia saat ini dan penerapan konsep restorative justice dalam penyelesaian perkara tindak pidana korupsi dimasa yang akan datang. Penelitian ini penting dilakukan sebagai masukan kepada pihak legislatif dalam pembetukan hukum dimasa yang akan datang. Jenis penelitian yang digunakan adalah penelitian hukum normatif. Penelitian ini mempunyai nilai kebaruan yakni mengkaji penerapan konsep restoratif Justice dalam penyelesaian perkara tindak pidana korupsi untuk mengefektifkan asas peradilan cepat, sederhana dan biaya ringan. Penelitian ini memiliki fokus kajian tentang penerapan konsep restorative justice dalam penyelesaian perkara tindak pidana korupsi dalam mewujudkan peradilan yang sederhana, cepat dan berbiaya ringan. Adapun hasil penelitian ini adalah sebagai berikut: Pertama, penegakan hukum pidana bagi pelaku tindak pidana korupsi di Indonesia saat ini mutlak dilakukan melalui proses peradilan artinya setiap tindak pidana korupsi baik yang jumlah kerugian keuangan negara besar maupun kecil harus melewati proses peradilan yang berakhir dengan putusan pemidanaan. Kedua, penerapan konsep restorative justice dalam penyelesaian perkara tindak pidana korupsi dalam penelitian ini hanya memfokuskan perkara tindak pidana korupsi yang nilai kerugiannya terbilang kecil yang dilakukan dengan cara pengembalian kerugian keuangan negara, pemberian denda dan pelaksanaan kerja sosial bagi pelaku yang mana dalam pelaksanaannya melibatkan pelaku, pemerintah dan aparat penegak hukum. Penerapan konsep restorative justice dalam penyelesaian perkara tindak pidana korupsi selain memaksimalkan pengembalian kerugian keuangan negara hasil korupsi, juga untuk mengurangi penggunaan keuangan negara yang jauh lebih besar daripada kerugian keuangan negara yang diakibatkan dari tindak pidana korupsi.